2023
DOI: 10.3390/lubricants11050224
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Effects of Metalworking Fluids in Cutting Processes

Abstract: An understanding of the proper application of metalworking fluids (MWFs) is necessary for their implementation in efficient production processes. In addition, the knowledge of the process-related aspect of chip transport and the macroscopic cooling effect, the characteristics and properties of lubricant film formation, and the cooling conditions in the secondary shear zone on the chip surface, i.e., in the direct vicinity of the material separation, represent a combined fundamental scientific issue within prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In prior research, Liu and Pape explored the suitability of the EHL ball-on-disc test rig, pin-on-ring, and pin-on-plate tribotesters for investigating metalworking fluids (MWF). Their studies revealed insights into the impact of boundary films on the frictional properties during metal cutting [15,16]. A previous research article considered employing a cylinderon-disc tribometer in order to evaluate frictional forces and wear values for different coated cylinders at long distances and a high sliding speed range of 0.5-3 m/s.…”
Section: Introductionmentioning
confidence: 99%
“…In prior research, Liu and Pape explored the suitability of the EHL ball-on-disc test rig, pin-on-ring, and pin-on-plate tribotesters for investigating metalworking fluids (MWF). Their studies revealed insights into the impact of boundary films on the frictional properties during metal cutting [15,16]. A previous research article considered employing a cylinderon-disc tribometer in order to evaluate frictional forces and wear values for different coated cylinders at long distances and a high sliding speed range of 0.5-3 m/s.…”
Section: Introductionmentioning
confidence: 99%